Utilization of NLP in Marketing Communications - Idris Kusumanegara; Mohammad Faisal Rahman (Budapest International Research and Critics University, 2022)
Words are part of almost every market interaction. Online reviews, customer service calls, press releases, marketing communications, and other interactions create a lot of textual data. But how do the best marketers use that data? This article provides an overview of automated textual NLP analysis and details how to use it to generate marketing insights. The author discusses how text can be a powerful tool both for prediction and for understanding (i.e., insight) and how NLP text can be used to unify marketing. The results show that textual analysis can unify many marketing components. While most marketing issues are interdisciplinary, the field is often fragmented. By engaging the skills and ideas from each of the marketing subfields, text analysis has the potential to help unify the field with a common set of tools and approaches.